2001
DOI: 10.1177/074873001129001935
|View full text |Cite
|
Sign up to set email alerts
|

Photoperiod Modulates the Inhibitory Effect of In Vitro Melatonin on Lymphocyte Proliferation in Female Siberian Hamsters

Abstract: In Siberian hamsters (Phodopus sungorus), short days suppress reproductive function and lymphocyte proliferation. To determine whether melatonin influences cell-mediated immunity through a direct action on lymphocyte proliferation, in vitro responsiveness to mitogens and melatonin was assessed in systemic and splenic lymphocytes from adult female Siberian hamsters housed in either long or short days for 13 weeks. Short days provoked reproductive regression and reduced lymphocyte proliferation. Physiological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
18
1

Year Published

2002
2002
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 24 publications
2
18
1
Order By: Relevance
“…It is apparent that gender differences exist concerning seasonal changes of lymphocyte subpopulations in the horse and this should be investigated further. The data from the present study are partially consistent with the previous studies performed in male and female hamsters [2,38,39]. But, these studies of hamster have typically been conducted under artificial photoperiodic conditions and therefore some physiological variables of the natural photoperiod might be masked by artificial light or artificial darkness [40].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…It is apparent that gender differences exist concerning seasonal changes of lymphocyte subpopulations in the horse and this should be investigated further. The data from the present study are partially consistent with the previous studies performed in male and female hamsters [2,38,39]. But, these studies of hamster have typically been conducted under artificial photoperiodic conditions and therefore some physiological variables of the natural photoperiod might be masked by artificial light or artificial darkness [40].…”
Section: Discussionsupporting
confidence: 91%
“…However, others have reported on seasonal variations of white blood cells including lymphocytes in the horse [36,37]. In addition, it has been reported that in Siberian hamsters, long-day breeders like horse, photoperiodic changes in immune function are observed [2,38,39]. In the present study, we found that a gender-by-day length interaction on lymphocyte subpopulations suggest that only stallions responded to photoperiod whereas mares were not responsive.…”
Section: Discussioncontrasting
confidence: 55%
“…However, in other rodents, splenocytes, bone marrow cells, and lymphoid cells in the circulation all possess functional MEL receptors, and MEL treatments in vitro enhance or suppress immune responses in a cell- and antigen-specific manner (e.g., Pozo et al, 1997). In hamsters, MEL can inhibit or stimulate lymphocyte and splenocyte proliferation in vitro, depending on sex, age and photoperiod (Prendergast et al, 2001; 2002b). This is consistent with other reports in deer mice, in which exogenous MEL in vivo has been reported to enhance splenocyte proliferation in vitro, although MEL treatments did not inhibit primary immunoglobulin M antibody production (Demas & Nelson, 1998).…”
Section: Transduction Of Photoperiod Cuesmentioning
confidence: 99%
“…Zhou et al (2002) provide evidence for effects of day length on immune measures (auricular lymphocyte counts) and responses (IL-6 production in sensitized lymphocytes, mitogen-stimulated T-cell blastogenesis). This is, of course, not the first report indicating effects of photoperiod on immune responses in a reproductively photoperiodic species (e.g., , nor is it the first report indicating the absence thereof (e.g., Prendergast et al, 2001). We agree with the statement of Zhou et al that it is important to discover any functional significance to the photoperiodic and melatonin-induced changes in immune measures and responses reported by many authors for several mammalian species (Blom et al, 1994;Demas and Nelson, 1998;Yellon, Teasley, et al, 1999;Drazen et al, 2000;Mann et al, 2000;Prendergast et al, 2001;Prendergast et al, 2002;Yellon and Tran, 2002); however, we do not view the majority of data published to date on effects of photoperiod on immunity as adequate tests of immune function (as described above).…”
mentioning
confidence: 81%